Failure analysis of solar wheel broken teeth of wind turbine yaw drives - LI Xuwang; HUANG Chengyan; LI Guifang; FAN Huan; WANG Han; WEI Yufeng (Jixie chuandong)
ObjectiveThe fatigue load of the yaw system is the main cause of wind turbine failures, and the phenomenon of gear and shaft breakage in yaw drive and other gearboxes is still a high-frequency fault. The failure analysis results indicate that the production process of raw materials, organizational control results, macroscopic mechanical performance adjustment, component assembly clearance, meshing relationship, and vibration influence are the main causes of failure. By studying and analyzing these patterns, the cause of tooth breakage in the output teeth of the sun gear in the yaw drive gearbox of onshore wind turbines can be identified, providing technical support for the subsequent research and design of wind turbine yaw systems.MethodsThrough physical and chemical performance testing of failed output teeth and SEM fracture analysis, the gear structure design and unit operating status were investigated to determine the cause of tooth breakage.ResultsThe results show that the abnormal decomposition of the martensitic structure on the surface layer of the output tooth resulted in a surface hardness below 58 HRC and a shallower hardening layer depth by 10%, which reduced the surface contact strength of the tooth. Multiple non-metallic inclusions about 5 micrometers were found on the fracture surface, and rough machining marks on the tooth root surface further reduced the bending strength of the tooth root. During operation, the effective meshing area between the gear racks was only 50%, indicating severe uneven loading. This resulted in the working stress of the teeth exceeding the allowable stress, triggering fatigue wear and early cracking on the tooth surface, and causing tooth fracture when the load exceeds the bearing limit. The phenomenon of partial load broken tooth is improved after machining technique and tooth shape optimization.